Persuasive Communication of the Indonesian Family Planning Association in Instilling Islamic Values in Foster Children at LPKA Class II Bandar Lampung - Sausan Haura; Khairullah Khairullah; Siti Wuryan (Jurnal Ilmiah Syi'ar, 2026)
The high number of children in conflict with the law in Indonesia reflects a moral crisis that demands value-based rehabilitation rather than mere punishment. At the Class II Special Juvenile Correctional Institution (LPKA) in Bandar Lampung, 114 out of 118 juvenile detainees are Muslim, yet structured Islamic valuebased guidance remains limited. Unlike LPKA facilities in other cities that rely primarily on internal officers for religious programming, LPKA Class II Bandar Lampung stands out as a site where an external organization, the Indonesian Planned Parenthood Association (PKBI), actively conducts an inclusion-based program using persuasive communication. This makes it a scientifically relevant and strategically significant research setting. This study examines the persuasive communication employed by PKBI in instilling Islamic values among juvenile detainees at this institution. Juvenile offenders in conflict with the law require a humanistic, empathetic, and morally grounded approach to support their rehabilitation process. This study employs a descriptive qualitative method with data collected through in-depth interviews, non-participant observation, and documentation. Informants were selected through purposive sampling, comprising PKBI program staff, LPKA officers, and juvenile detainees. The theoretical framework draws on Carl I. Hovland’s attitude change theory, which emphasizes the roles of communicator credibility, message quality, and audience conditions in the persuasion process. The findings reveal that PKBI applies four persuasive communication strategies, namely psychodynamic, socio-cultural, meaning construction, and mirror strategies, to convey Islamic values encompassing aqidah, shari’ah, and akhlak to the juvenile detainees.